The Study of Flood Discharge in Ujong Krueng in the Tripa Watershed - Putri Maulina Devi; Meylis Safriani; M. Faisi Ikhwali (Litbang Pemas - Universitas Islam Lamongan, 2022)
The Krueng Tripa River is located Nagan Raya Regency that is vunerability to flooding. Administratively Krueng Tripa flows through two regencies in Aceh Province, namely Gayo Lues Regency in the upper reaches of the river and Nagan Raya Regency in its downstream with an area of watershed covering 2953,457 km². The rainfall in this watershed is around 2,197 mm per year. High rainfall has a major impact on flood disasters and has a negative impact on the surrounding community.The purpose and benefits of this study are to determine the magnitude of the flood discharge of the Krueng Tripa River and as input for related darta in flood mitigation problems. Analysis of the flood discharge using the Synthesis Unit Hydrograph (HSS) Gama I method. From the analysis using the distribution of log person III with return periods of 2, 5, 10, 25, 50, and 100 years, it were obtained respectively 141,520 mm, 192,349 mm; 227.094 mm; 272.270 mm; 306,569 mm; 341,869 mm. The results of the flood analysis in the Krueng Tripa River using the HSS Gama I method with return periods of 2, 5, 10, 25, 50, and 100 years in a row are 3419,276 m³/s; 4647.384 m³/s; 5486.740 m³/s; 6578,338 m³/s; 6702.133 m³/s; 8259.949 m³/s.